Phosphorescent iridium(III) complexes bearing l-alanine ligands: Synthesis, crystal structures, photophysical properties, DFT calculations, and use as chemosensors for Cu2+ ion. (February 2021) - Li, Zhenbiao; Ge, Zerong; Tong, Xin; Guo, Lanying; Huo, Jiale; Li, Dongchan; Li, Hongyan; Lu, Aidang; Li, Tianyi
Abstract: Two neutral iridium complexes with l -alanine as ancillary ligands, (thp)2 Ir (l -alanine) (Ir1 ) (thp = 2-(thiophen-2-yl)pyridine) and (btp)2 Ir (l -alanine) (Ir2 ) (btp = 2-(benzo[ b ]thiophen-2-yl)pyridine) were synthesized and investigated. The solid-state structures of the developed Ir1 and Ir2 were authenticated by single X-ray diffraction. Ir(III) complexes Ir1 and Ir2 exhibit intense yellow and red emission respectively with high quantum efficiencies ( Φ em = 0.88 for Ir1, Φ em = 0.29 for Ir2 ) in oxygen-free acetonitrile solution at room temperature. Theoretical calculations were carried out to provide a further study of the orbital distributions and electronic states of the two complexes. The two complexes displayed significant reversible phosphorescence quenching upon binding to Cu 2+ ion and the binding stoichiometry was approximately 1:1. 1 H NMR titration experiments indicated that coordination of Cu 2+ to the nitrogen atoms of the l -alanine ligands of the complexes induce the significant variations in optical signals. This work showed that new phosphorescent probes based on iridium complexes could be realized by introducing simple amino acid ancillary ligands. Graphical abstract: Image 1 Highlights: Two neutral Ir(III) complexes with l -alanine as ancillary ligands were synthesized. These two Ir(III) complexes exhibit strong phosphorescence with high quantum efficiencies. These two complexes bearing l -alanine can be used as efficient selective sensors for the Cu 2+ ion.